Sains Islam VS Sains Barat: Analisis Amalan dan Perbandingan - Vina Atiqatul Maula; Alfina Wildatul Fitriyah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Islamic science and Western science are two rich scientific traditions with a long history and significant contributions to science. Despite some similarities, they also have fundamental differences in methodology, epistemology, and goals. Islamic science flourished during the Middle Ages, driven by intellectual curiosity and the urge to understand God's creation. Muslim scientists combined the revelations of the Koran with observations and experiments to produce advances in a variety of fields, including astronomy, mathematics, physics, optics, and medicine. They emphasized the importance of a systematic scientific method, using hypotheses, experiments, and observations to test theories.Western science, on the other hand, emerged in Europe during the Renaissance and Enlightenment. Western science is characterized by its emphasis on rationalism, empiricism, and secularism. Western scientists challenged the authority of religion and tradition, and focused on developing more rigorous scientific methods, such as controlled experiments and testable hypotheses.